2021
DOI: 10.5539/cis.v14n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Public Attitudes toward E-Government Health Applications Used During the COVID-19 Pandemic: Evidence from Saudi Arabia

Abstract: This study sought to explore factors that determine the public’s acceptance of and adoption behavior toward e-government health applications launched in Saudi Arabia (SA) by the Ministry of Health (MOH) during the COVID-19 pandemic. The research relied on several theories: the technology acceptance model (TAM), information system success model (ISSM), mobile services acceptance model (MSAM), and unified theory of acceptance and use of technology (UTAUT). The constructs of perceived ease of use (PEOU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The influence of functionality on the CUI (H6b) was not affirmed, thus contradicting past research findings [ 64 ]. The present study supported H7a and H7b, which stated that information quality has a critical effect on satisfaction and the CUI; these results are consistent with those of preceding studies [ 26 , 27 , 41 ]. Moreover, the impacts of engagement on satisfaction (H8a) and the CUI (H8b) were recognized by both the current and former studies [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The influence of functionality on the CUI (H6b) was not affirmed, thus contradicting past research findings [ 64 ]. The present study supported H7a and H7b, which stated that information quality has a critical effect on satisfaction and the CUI; these results are consistent with those of preceding studies [ 26 , 27 , 41 ]. Moreover, the impacts of engagement on satisfaction (H8a) and the CUI (H8b) were recognized by both the current and former studies [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Prior research confirmed that improved information quality enhances patients’ attitudes about telemedicine services [ 26 , 27 ]. Moreover, its usefulness encourages consumers to use the telehealth system in the future and advise others to do the same [ 41 ]. Based on these, we propose the following hypothesis:…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While a qualitative extension to this study to explore identified factors in more depth with health managers is planned, the research using the UTAUT model in Saudi Arabia continues to expand [16,[61][62][63]. Indeed in the interim, UTAUT has been adopted to consider eHealth literacy and personal EHR [58], eGovernment health applications [62], pandemic surveillance during the CO-VID-19 outbreak in KSA [63]. Clearly the UTAUT model resonates with practitioners and policy makers in KSA, so this is an opportune time to share the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested there is still a need to carry out more research investigating whether adding external constructs to the theory, reducing the current constructs, or modifying the moderators could make a difference to the overall picture the theory is trying to explain [60]. Since this study has been conducted, several research teams have adopted the UTAUT in eHealth studies, including in KSA but none with health managers [61][62][63].…”
Section: Strengths and Limitationsmentioning
confidence: 99%